The Slovak-Hungarian struggles in the interpretation of the common history - Grzesik, Ryszard (Balcanica Posnaniensia. Acta et studia, 2012)
The aim of the article is to search the roots of complicated Slovak-Hungarian relationship, which lies deeper than in the 19th century. Different interpretations of the role of the Slavs in the Hungarian state resulted in the creation of two national historiographies at the end of the 18th century, the Hungarian and the Slovak. I tried to compare them. It is to observe that recently the historians from both countries, Slovakia and Hungary started to discuss on the facts from their common history. It creates the optimistic perspectives for the future. First, I analyzed the image of the Pannonian Slavs in the Hungarian chronicles (Story of a white horse presented by the Anonymous Notary of King Béla and by the Chronicle composition of the 14th century). Moreover, I analyzed the information about this ruler in the Bohemian and South-Slavic (the Chronicle of Duklja) tradition, underlining the functional identity of Svatopluk of the Duklja Chronicle with Aquila/Atyla of the Hungarian-Polish Chronicle.